Plasma extracellular vesicle messenger RNA profiling identifies prognostic EV signature for non-invasive risk stratification for survival prediction of patients with pancreatic ductal adenocarcinoma - Han, Yi; Drobisch, Pascal; Krüger, Alexander; William, Doreen; Grützmann, Konrad; Böthig, Lukas; Polster, Heike; Seifert, Lena; Seifert, Adrian; Distler, Marius; Pecqueux, Mathieu; Riediger, Carina; et al. (Journal of hematology & oncology, 2023)
The prognosis of pancreatic ductal adenocarcinoma (PDAC) is one of the most dismal of all cancers and the median survival of PDAC patients is only 6-8 months after diagnosis. While decades of research effort have been focused on early diagnosis and understanding of molecular mechanisms, few clinically useful markers have been universally applied. To improve the treatment and management of PDAC, it is equally relevant to identify prognostic factors for optimal therapeutic decision-making and patient survival. Compelling evidence have suggested the potential use of extracellular vesicles (EVs) as non-invasive biomarkers for PDAC. The aim of this study was thus to identify non-invasive plasma-based EV biomarkers for the prediction of PDAC patient survival after surgery.
Gesehen am 24.04.2023